Pengaruh Gamifikasi Pembelajaran Matematika Terhadap Hasil Belajar Peserta Didik Kelas VII SMP Negeri 5 Padangsidimpuan - Mona Chairani; Adek Nilasari Harahap; Nurdalilah (JURNAL CERMATIKA, 2025)
This study aims to determine the effect of gamification in mathematics learning on the academic achievement of seventh-grade students at SMP Negeri 5 Padangsidimpuan. The research employed a quasi-experimental method with a non-equivalent control group design. The sample consisted of two classes: an experimental group that received gamified instruction and a control group that was taught using conventional methods. Data were collected through learning outcome tests, and the analysis was conducted using parametric statistics, specifically the independent samples t-test. The analysis revealed that the average learning outcome in the experimental group was 83.6, which was higher than that of the control group, which had an average score of 76.2. The prerequisite tests indicated that the data were normally distributed and homogeneous. The t-test produced a significance value of p = 0.003 < 0.05, indicating a statistically significant difference between the two groups. The conclusion of this study is that gamified learning has a positive impact on students' mathematics achievement. Gamification enhances student engagement, motivation, and conceptual understanding. Therefore, this strategy is recommended as an innovative approach to mathematics instruction at the junior high school level.